An overview of process systems engineering approaches for process intensification: State of the art - Tian, Yuhe; Demirel, Salih Emre; Hasan, M.M. Faruque; Pistikopoulos, Efstratios N. (Chemical engineering and processing, 2018)
[Display omitted] •A survey of the state-of-the-art process systems engineering (PSE) approaches for process intensification.•An overview of the development of various process intensification technologies.•Survey of recent advances in modeling, design, and synthesis of intensified systems.•Assessment methods for the controllability/operability/safety performance of intensified process systems. Process intensification offers the potential to drastically reduce the energy consumption and cost of producing chemicals from both bulk and distributed feedstocks. This review article aims to offer an extensive survey on state-of-the-art process systems engineering (PSE) approaches for process intensification. From both academic and industrial perspectives, this paper provides an overview of the development of various process intensification technologies, specifically those under the categories of separation, reaction, hybrid reaction/separation, and alternative energy sources. A current status analysis in the areas of modeling and simulation is then provided. An indicative list of PSE publications specialized on process intensification is presented to illustrate the progresses made so far towards the deployment of novel process intensification technologies. We also highlight some recent advances for the modeling, design, and synthesis of intensified systems, as well as for the assessment of their controllability/operability/safety performance. Key open questions in these areas include: (i) how to systematically derive intensified designs, and (ii) how to ensure the operability and optimality of the derived intensified structures while delivering their expected functionality.